Rainbow Connection Number of Special Graph and Its Operations - Nastiti, Artanty; Dafik, Dafik (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
Let G be a simple graph. An edge-coloring of a graph G is rainbow connected if, for any two vertices of G, there are k internally vertex-disjoint paths joining them, each of which is rainbow and then a minimal numbers of color G is required to make rainbow connected. The rainbow connection numbers of a connected graph G, denoted rc(G). In this paper we will discuss the rainbow connection number rc(G) for some special graph andÂ its operations, namely crown product of P_2 igodot Pr_n, tensor product of P_2 igotimes W_n.